Investing in agricultural water management to benefit smallholder farmers in Burkina Faso. - Evans, Alexandra E.V.; Giordano, Meredith A.; Clayton, Terry (International Water Management Institute, 2012)
This Working Paper summarizes research conducted as part of the AgWater Solutions Project in Burkina Faso between 2009 and 2012. Researchers from the AgWater Solutions Project examined the potential for small reservoirs, inland valley cultivation and the use of motorized pumps. The main findings indicate that (1) Small reservoirs need better management at all stages to reduce costs and improve equity.Costs could be comparable with other AWM options. The total investment to reach 50% of the potential demand in Burkina Faso could be as much as USD 1,136 million. Costs could be reduced by tightly controlling planning, implementation and management, and should be compared with all the benefits over the lifetime of the reservoir. If implemented, some 321,000 households are likely to benefit; (2) Inland valleys, commonly known as bas fonds, can be used to increase rice cultivation as well as other crops through improved water management, agronomic and post-harvest practices. Investment in physical infrastructure and extension could amount to USD 384 million; (3) Motor pumps can increase yields and incomes, but problems in areas, such as financing, cost reduction of electricity supply, distance to pump suppliers, poor operation practices and maintenance, and environmental damage need to be addressed. Motor pumps used upstream of reservoirs can support profitable dry-season vegetable cultivation, but care must be taken regarding over-abstraction, pollution and conflicts. Greater adoption of motor pumps could benefit some 332,000 farming households irrigating up to 4% of the total agricultural land area at a total investment cost of USD 121 million; and (4) Combination of a range of agricultural water management options ? capture/storage+ lifting + irrigation technologies + soil conservation + watershed management ? arerecommended to enable supplementary irrigation in areas where dry spells become a common occurrence.